Inhibition of Fas expression by RNAi modulates 5-fluorouracil-induced apoptosis in HCT116 cells expressing wild-type p53 - Borralho, Pedro M. (2015)
Drug resistance to 5-fluorouracil (5-FU) is still a major limitation to its clinical use. In addition, the clinical value of p53 as a predictive marker for 5-FU-based chemotherapy remains a matter of debate. Here, we used HCTI 16 human colorectal cancer c